2013
DOI: 10.1016/j.jcma.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Alleviative effects of deep-seawater drinking water on hepatic lipid accumulation and oxidation induced by a high-fat diet

Abstract: DSW shows a preventive effect on development of hepatosteatosis induced by a high-fat diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
3
22
1
1
Order By: Relevance
“…In particular, drinking of DSW with high levels of Mg reduced serum lipids [32] and alleviated hepatic lipid accumulation and oxidation induced by high-fat diet [11] [33]. We also found that BDSW suppressed circulating triglycerides levels, except total cholesterol level, in the liver of STZ induced diabetic mice.…”
Section: Discussionmentioning
confidence: 53%
“…In particular, drinking of DSW with high levels of Mg reduced serum lipids [32] and alleviated hepatic lipid accumulation and oxidation induced by high-fat diet [11] [33]. We also found that BDSW suppressed circulating triglycerides levels, except total cholesterol level, in the liver of STZ induced diabetic mice.…”
Section: Discussionmentioning
confidence: 53%
“…DSW consumption lowers the lipid profile, levels of serum thiobarbituric acid-reactive substances, and lipid peroxidation levels in hypercholesterolemic subjects and increases antioxidant enzyme glutathione peroxidase-1 activity [4], [5], [28], possibly due to its high Mg 2+ and Ca 2+ content. Bathing in a magnesium-rich Dead Sea salt solution improves skin barrier function, enhances skin hydration, and reduces inflammation in atopic dry skin [29].…”
Section: Discussionmentioning
confidence: 99%
“…DSW is able to give protection for hepatic problems. In a study by Chen et al [33], it has decreased the lipid accumulation in livers, which are associated with the increase in daily faecal lipid and bile acid outputs. The hepatic antioxidative levels were also improved by its application, which were proven by the high capacity levels of liver glutathione and trolox equivalent antioxidant.…”
Section: Potential Benefits Of Deep Sea Water To Healthmentioning
confidence: 99%
“…DSW was able to regulate hepatic fatty acid homeostasis by upregulating genes related to b-oxidation of fatty acids, which are hepatic peroxisome proliferator-activated receptor-alpha, retinoid X receptor-alpha, and uncoupling protein-2 gene expression. Its application can attenuate hepatic damage, which is proven by reduced lipid peroxidation status in livers, which might be related to reducing hepatic malondialdehyde (MDA) content [33]. The liver damage indices which are aspartate aminotransferase (AST) and alanine aminotransferase (ALT) are also reduced by its application.…”
Section: Potential Benefits Of Deep Sea Water To Healthmentioning
confidence: 99%